Adverse reactions to 1975 bivalent influenza vaccine in children. - Schevill, S. (1977)
A questionnaire survey was undertaken to investigate incidence and types of reactions to a bivalent, zonally purified, killed influenza vaccine administered to 155 children aged 1 to 18 years in 1975. Local or systemic reactions or both occurred in 42 children (27%). However, these reactions were not considered serious and should not constitute a major drawback to future influenza programs in children under 3 years of age.